Kraft-Schnellkraft-Sportarten - Stafilidis, S.; Arampatzis, A. (Journal of Sports Sciences, 2007)
The aim of this study was to test the hypothesis that sprint performance (time over a given distance) would be affected by track compliance, with better performances on the more compliant surface. Ten sprinters participated in the study. The athletes performed maximal sprints (60 m) on three different track configurations (hard, 5500 kN/m; soft, 2200 kN/m; spring, 550 kN/m). A 60-m single-lane running surface was constructed. Plywood boards (1.2 cm thick) were placed on a 60 × 0.6 m wooden chipboard frame serving as the base surface. All participants ran two times on each track configuration in a randomized order. The athletes' kinematics were recorded using the Vicon 624 system with 12 cameras operating at 250 Hz. Four Kistler force plates (1250 Hz) were used to record ground reaction forces. Sprint performance (time over 60 m) was unaffected by the different track compliances (P = 0.57). In addition, there was no effect of track (P > 0.05) on the sprinting kinematics and kinetics of the ankle or knee joint. The hypothesis that sprint performance is affected by track compliance can be rejected because the sprinters recorded similar performances while sprinting over 60 m on all three track configurations. We conclude that: (1) the possible deformation of the track while sprinting is minor enough not to cause a specific adjustment in the leg mechanics affecting the effectiveness of the stretch - shortening cycle of the sprinters; and (2) the energy exchange between sprinters and tracks has only a marginal effect on sprint performance due to its small magnitude. More research on tracks with lower stiffness is required.